1994
DOI: 10.1002/jcu.1870220405
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis of the thyroid gland: Role of ultrasonography

Abstract: We studied the role of ultrasound assessment of the thyroid gland in detecting amyloid deposition in 9 patients confirmed to have renal amyloidosis because the thyroid gland is a readily accessible organ. Ultrasound examination of the thyroid gland showed a distinctive abnormal appearance in 7 patients. There was enlargement of one or both lobes of the thyroid, a high echogenicity approaching that of the surrounding connective tissue, and a very fine homogeneous echotexture similar to ground glass appearance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…T-99 pyrophosphate, ultrasound computed tomography, and magnetic resonance imaging studies are nonspecific (12). Hyperechoic feature and fine homogeneous texture of the goiter have been described at ultrasound examination (13). Fine-needle aspiration biopsy may facilitate the diagnosis of amyloid goiter (14,15), however amyloid deposition in the thyroid is not limited to amyloid goiter and is seen in association with medullary carcinoma and plasma cell dyscrasias.…”
Section: Discussionmentioning
confidence: 97%
“…T-99 pyrophosphate, ultrasound computed tomography, and magnetic resonance imaging studies are nonspecific (12). Hyperechoic feature and fine homogeneous texture of the goiter have been described at ultrasound examination (13). Fine-needle aspiration biopsy may facilitate the diagnosis of amyloid goiter (14,15), however amyloid deposition in the thyroid is not limited to amyloid goiter and is seen in association with medullary carcinoma and plasma cell dyscrasias.…”
Section: Discussionmentioning
confidence: 97%
“…Our sonographic findings of increased reflectivity and altered echotexture are compatible with the ground-glass appearance described by el-Reshaid et al . 10 The cysts, though lobular, were simple in appearance without the internal components as reported by Fontan et al . 11…”
Section: Discussionmentioning
confidence: 59%
“…At ultrasound, in addition to uni- or bi-lobar thyroid enlargement, many report a marked increase in thyroid reflectivity approaching that of the surrounding connective tissue, 3, 5 as a result of fatty infiltration within the thyroid. 9 A very fine homogeneous echotexture similar to ground glass appearance 10 has also been described, whereas focal areas of reduced reflectivity are seen with more localized amyloid deposits.…”
Section: Discussionmentioning
confidence: 88%
“…In the present case, neither hemorrhage nor cyst nor fatty infiltration were seen in the histological examination of wedge resection biopsy of the thyroid gland. El-Reshaid et al (1994) reported a high echogenicity of a very fine homogenous echotexture in 3 cases with diffuse amyloid goiter. The utrasound findings in the present case were similar to these.…”
Section: Discussionmentioning
confidence: 97%